Sequence and structural analysis of surface protein antigen I/II (SpaA) of Streptococcus sobrinus. - LaPolla, R J (1991)
Streptococcal antigen I/II or the surface protein antigen A (SpaA) of Streptococcus sobrinus is an adhesin which mediates binding of the organism to tooth surfaces. The complete sequence of the gene which encodes SpaA has been determined. The gene consists of 4,584 bp and encodes a protein of 1,528 amino acid residues. The deduced amino acid sequence shows extensive homology with those of the cell surface adhesins from Streptococcus mutans serotypes c and f and from Streptococcus sanguis. Structural analysis of the N-terminal region (residues 50 to 550), which is rich in alanine and includes four tandem repeats of an 82-residue sequence, suggests that it adopts an alpha-helical coiled-coil conformation. Cell surface hydrophobicity may be associated with this region. The C-terminal region is more conserved and includes two tandem repeats of a 39-residue proline-rich sequence. A further proline-rich sequence in this region is predicted to span the cell wall. Although a hydrophobic sequence is present in the C-terminal region, it appears to be too short to span the cell membrane. Anchoring of SpaA in the cell membrane may therefore require some form of posttranslational modification or association with another membrane protein.